Bronchiectasis is associated with delayed diagnosis and adverse outcomes in the New Zealand Common Variable Immunodeficiency Disorders cohort study. (12th April 2021) - Ameratunga, R; Jordan, A; Cavadino, A; Ameratunga, S; Hills, T; Steele, R; Hurst, M; McGettigan, B; Chua, I; Brewerton, M; Kennedy, N; Koopmans, W; et al.
Summary: Common variable immunodeficiency disorders (CVID) are multi-system disorders where target organ damage is mediated by infective, autoimmune and inflammatory processes. Bronchiectasis is probably the most common disabling complication of CVID. The risk factors for bronchiectasis in CVID patients are incompletely understood. The New Zealand CVID study (NZCS) is a nationwide longitudinal observational study of adults, which commenced in 2006. In this analysis, the prevalence and risk factors for bronchiectasis were examined in the NZCS. After informed consent, clinical and demographic data were obtained with an interviewer-assisted questionnaire. Linked electronic clinical records and laboratory results were also reviewed. Statistical methods were applied to determine if variables such as early-onset disease, delay in diagnosis and increased numbers of infections were associated with greater risk of bronchiectasis. One hundred and seven adult patients with a diagnosis of CVID are currently enrolled in the NZCS, comprising approximately 70% of patients known to have CVID in New Zealand. Fifty patients (46·7%) had radiologically proven bronchiectasis. This study has shown that patients with compared to those without bronchiectasis have an increased mortality at a younger age. CVID patients with bronchiectasis had a greater number of severe infections consequent to early-onset disease and delayed diagnosis. Indigenous Māori have a high prevalence of CVID and a much greater burden of bronchiectasis compared to New Zealand Europeans. Diagnostic latency has not improved during the study period. Exposure to large numbers of infections because of early-onset disease and delayed diagnosis was associated with an increased risk of bronchiectasis. Earlier diagnosis and treatment of CVID may reduce the risk of bronchiectasis and premature death in some patients. Graphical Abstract: